A rendszer változik a módszer marad? A közigazgatási térfelosztás és a nemzeti kérdés kapcsolatának összehasonlító elemzése - Gulyás, László (Közép-Európai Közlemények, 2017)
Our essay consist of threee parts. In the first part I will introduce 3 executive spatial reform (1919, 1923, 1928) of First Chechoslovak Rebublik. The second part of this essay I am investigating the attempt of administrative reform (1993) and administrative reforms (1996) of the Slovak Republic. We called it regionalisation. At the same time the Hungarian minority of Slovakia elaborated a different version of the administrative reform – for example resolution of the general assembly of Komarno of 6th of January 1994. –, which suited their interests better. We called it etnoregionalism. Int the third part of this essay I compare the 3 executive spatial reform made in Czechoslovakia between two world war and the executive reform happened Slovakia during the Meciar-era. The conclusion of our essay is: The system is changing, but the method are the same!